Effect of Highly and Least Adsorbed Component on Sandwiching Recoil Chromatographic Separation - Ghimire, Kedar Nath; Ishida, Masaru (Tribhuvan University Journal, 2011)
Available with full text Key words: Sandwiching Recoil; Chromatographic Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 17-26 Uploaded date: 22 April, 2011